PENGARUH IKLAN DAN LAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA JUPITER MX - Muhammad Halilintar; Brahmadi Bagus (Fakultas Ekonomi Universitas Borobudur, 2018)
Based on the results of data analysis using path analysis through the SPSS program that was stated in the previous chapter, it can be concluded that several important things in this study are as follows.Correlation coefficients obtained are positive values that reflect that advertising and after sales have a positive relationship with purchasing decisions, so the higher the advertising and after sales, the higher the purchase decision. From the results obtained also known the coefficient of determination that reflects how much the contribution of independent variables (advertising and after-sales) to the dependent variable (decision purchase), namely 0.795 or 79.5%, meaning that advertising and after sales affect the purchase decision of 79.5 The remaining% of 20.5% is influenced by other factors not examined. Keywords: advertising, after-sales service, motorcycle purchase.